Kebijakan Pidana dalam Penanggulangan Pungutan Liar Pembuatan Kartu Tanda Penduduk oleh Oknum Dinas Kependudukan dan Catatan Sipil - Chairunnisa Keliat (CERED Indonesia, 2020)
Which is the focus of the problem in this research are; What are the forms of liar levies carried out by persons in the Population and Civil Registry Service, how to regulate and enforce criminal law for perpetrators of illegal levies making Identity Cards at the Population and Civil Registry Service, as well as how to control agencies that are regulated against illegal levies Making Identity Cards at the Population and Civil Registry Service. So that it can be drawn, among others, from the penalties, among others, criminal sanctions for civil servants who are extortionists subject to criminal sanctions in the form of imprisonment and criminal fines in accordance with the provisions of Article 368, Articles 418, 423, and 425 of the Criminal Code, and there are also stipulated in Article 95B of the Law Population Administration Act. Law enforcement for perpetrators of extortion is regulated in Article 40, Article 52 and Article 53 of the Law on Public Services. Law enforcement starts from internal enforcement carried out by superiors or heads of offices, law enforcement in a lawsuit due to losses due to extortion, and finally law enforcement through criminal justice. Asahan Dukcapil, law enforcement can also be done by internal action, and the legal process can be submitted to the BKD. The countermeasures against the practice of extortion of ID cards in Dukcapil can be carried out by threatened agencies in monitoring and overcoming the practice of extortion of VAW based on Article 40 paragraph (1) and Article 6 and Article 7 paragraph (1) and (2) of the Law Public Services, Government efforts in terms of preparing messages related to extortion law enforcement.